Safety and efficacy of leriglitazone for preventing disease progression in men with adrenomyeloneuropathy (ADVANCE): a randomised, double-blind, multi-centre, placebo-controlled phase 2–3 trial. Issue 2 (February 2023) - Köhler, Wolfgang; Engelen, Marc; Eichler, Florian; Lachmann, Robin; Fatemi, Ali; Sampson, Jacinda; Salsano, Ettore; Gamez, Josep; Molnar, Maria Judit; Pascual, Sílvia; Rovira, Maria; Vilà, Anna; et al.
Summary: Background: Adult patients with adrenoleukodystrophy have a poor prognosis owing to development of adrenomyeloneuropathy. Additionally, a large proportion of patients with adrenomyeloneuropathy develop life-threatening progressive cerebral adrenoleukodystrophy. Leriglitazone is a novel selective peroxisome proliferator-activated receptor gamma agonist that regulates expression of key genes that contribute to neuroinflammatory and neurodegenerative processes implicated in adrenoleukodystrophy disease progression. We aimed to assess the effect of leriglitazone on clinical, imaging, and biochemical markers of disease progression in adults with adrenomyeloneuropathy. Methods: ADVANCE was a 96-week, randomised, double-blind, placebo-controlled, phase 2–3 trial done at ten hospitals in France, Germany, Hungary, Italy, the Netherlands, Spain, the UK, and the USA. Ambulatory men aged 18–65 years with adrenomyeloneuropathy without gadolinium enhancing lesions suggestive of progressive cerebral adrenoleukodystrophy were randomly assigned (2:1 without stratification) to receive daily oral suspensions of leriglitazone (150 mg starting dose; between baseline and week 12, doses were increased or decreased to achieve plasma concentrations of 200 μg·h/mL [SD 20%]) or placebo by means of an interactive response system and a computer-generated sequence. Investigators and patients were masked to group assignment. The primary efficacy endpoint was change from baseline in the Six-Minute Walk Test distance at week 96, analysed in the full-analysis set by means of a mixed model for repeated measures with restricted maximum likelihood and baseline value as a covariate. Adverse events were also assessed in the full-analysis set. This study was registered with ClinicalTrials.gov, NCT03231878 ; the primary study is complete; patients had the option to continue treatment in an open-label extension, which is ongoing. Findings: Between Dec 8, 2017, and Oct 16, 2018, of 136 patients screened, 116 were randomly assigned; 62 [81%] of 77 patients receiving leriglitazone and 34 [87%] of 39 receiving placebo completed treatment. There was no between-group difference in the primary endpoint (mean [SD] change from baseline leriglitazone: –27·7 [41·4] m; placebo: –30·3 [60·5] m; least-squares mean difference –1·2 m; 95% CI –22·6 to 20·2; p=0·91). The most common treatment emergent adverse events in both the leriglitazone and placebo groups were weight gain (54 [70%] of 77 vs nine [23%] of 39 patients, respectively) and peripheral oedema (49 [64%] of 77 vs seven [18%] of 39). There were no deaths. Serious treatment-emergent adverse events occurred in 14 (18%) of 77 patients receiving leriglitazone and ten (26%) of 39 patients receiving placebo. The most common serious treatment emergent adverse event, clinically progressive cerebral adrenoleukodystrophy, occurred in six [5%] of 116 patients, all of whom were in the placebo group. Interpretation: The primary endpoint was not met, but leriglitazone was generally well tolerated and rates of adverse events were in line with the expected safety profile for this drug class. The finding that cerebral adrenoleukodystrophy, a life-threatening event for patients with adrenomyeloneuropathy, occurred only in patients in the placebo group supports further investigation of whether leriglitazone might slow the progression of cerebral adrenoleukodystrophy. Funding: Minoryx Therapeutics.